Positive electrode sheet, secondary battery, and electronic device
Patent Information
- Application Number
- CN202580004095.0
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2025-02-14
- Publication Date
- 2026-10-20
AI Technical Summary
In existing technologies, increasing the content of positive electrode conductive agent when reducing the internal resistance of lithium-ion batteries can affect energy density, while reducing the content of binder can reduce adhesion, leading to problems such as demolding and thickness expansion.
Carbon nanotubes with a dendritic structure are used as the positive electrode conductive agent, and their diameter and the longest branch length are controlled within a specific range to form a well-connected conductive network. Combined with an appropriate amount of carbon black particles and binder, the composition of the positive electrode sheet is optimized.
It improves the conductivity and lithium-ion transport efficiency of the positive electrode, reduces the internal resistance of the secondary battery, and maintains high energy density and adhesion while reducing thickness expansion.
Abstract
Description
Positive electrode plate, secondary battery and electronic device Technical Field
[0001] This application relates to the field of electrochemical technology, and in particular to a positive electrode, a secondary battery, and an electronic device. Background Technology
[0002] Lithium-ion rechargeable batteries possess advantages such as high energy density, high open-circuit voltage, low self-discharge rate, long cycle life, and good safety, and are widely used in various fields such as energy storage, mobile electronic devices, electric vehicles, and aerospace equipment. With the rapid development of mobile electronic devices and electric vehicles, the market has consistently sought to achieve even lower internal resistance in lithium-ion rechargeable batteries.
[0003] Existing technologies often reduce the internal resistance of lithium-ion batteries by increasing the content of the positive electrode conductive agent or decreasing the content of the binder in the positive electrode sheet. However, increasing the content of the positive electrode conductive agent often reduces the content of the positive electrode active material, affecting the energy density of the lithium-ion battery; while reducing the binder content reduces the cohesive force of the positive electrode active material layer itself, or reduces the adhesion between the positive electrode active material layer and the positive electrode current collector, leading to problems such as demolding and thickness expansion during the use of the lithium-ion battery. Therefore, developing a new technical solution to reduce the internal resistance of lithium-ion batteries has become a technical problem that urgently needs to be solved by those skilled in the art. Summary of the Invention
[0004] The purpose of this application is to provide a positive electrode, a secondary battery, and an electronic device to reduce the internal resistance of the secondary battery.
[0005] It should be noted that while this application uses lithium-ion batteries as an example of secondary batteries to explain the invention, the secondary batteries in this application are not limited to lithium-ion batteries. The specific technical solution is as follows:
[0006] The first aspect of this application provides a positive electrode sheet, comprising a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. The positive active material layer includes a positive conductive agent, which comprises carbon nanotubes with a dendritic structure. The diameter of the carbon nanotubes is 3 nm to 15 nm, and the length of the longest branch in the carbon nanotube is 5 μm to 30 μm. The carbon nanotubes with a dendritic structure, used as a positive conductive agent, have low impedance and provide good conductivity. The positive electrode sheet of this application, by selecting the aforementioned carbon nanotubes as the positive conductive agent and controlling the diameter of the carbon nanotubes and the length of the longest branch within the range of this application, makes the conductive network formed by the carbon nanotubes coherent, thereby improving electron transport efficiency and increasing the conductivity of lithium ions (Li). +The transport paths along the surface of carbon nanotubes are more abundant. Furthermore, the carbon nanotubes of this application have a dendritic structure, resulting in more uniform dispersion than non-dendritic carbon nanotubes. This allows for better uniformity and thinness when coated on the surface of the positive electrode active material, making it easier to achieve good conductivity. Therefore, through the above configuration, the positive electrode sheet exhibits good conductivity, and when used in a secondary battery, the secondary battery has lower internal resistance.
[0007] In one embodiment of this application, different branches of carbon nanotubes are connected by molecular covalent bonds.
[0008] In one embodiment of this application, the mass percentage of carbon nanotubes is 0.05% to 2% based on the mass of the positive electrode active material layer. By controlling the diameter of the carbon nanotubes within the above range, the positive electrode sheet has good conductivity, and electron and lithium ion transport efficiency is good.
[0009] In one embodiment of this application, the positive electrode sheet satisfies at least one of the following characteristics: (1) the diameter of the carbon nanotubes is 5 nm to 10 nm; (2) the length of the longest branch in the carbon nanotubes is 8 μm to 20 μm; (3) the mass percentage of carbon nanotubes is 0.1% to 0.5%. This is beneficial for improving the conductivity of the positive electrode sheet. When the positive electrode sheet is applied to a secondary battery, the secondary battery has a lower internal resistance.
[0010] In one embodiment of this application, the carbon nanotubes have 3 to 10 branches. By controlling the branching of the carbon nanotubes within the above range, the positive electrode exhibits good conductivity. The secondary battery using the positive electrode has low internal resistance.
[0011] In one embodiment of this application, the carbon nanotubes have 4 to 10 carbon layers. By controlling the number of carbon layers within this range, the positive electrode exhibits good electrical conductivity. The secondary battery using this positive electrode has low internal resistance.
[0012] In one embodiment of this application, the positive electrode active material layer further includes a positive electrode active material, and carbon nanotubes are disposed on the surface of the positive electrode active material particles, with the thickness of the carbon nanotubes disposed on the surface of the positive electrode active material being 5 nm to 20 nm.
[0013] In one embodiment of this application, the spacing between two adjacent carbon nanotubes disposed on the surface of the positive electrode active material is d, and the coefficient of variation of d is 0.5% to 5%. Adjusting the coefficient of variation of d within the above range indicates that the carbon nanotubes are uniformly distributed on the surface of the positive electrode active material.
[0014] In one embodiment of this application, the positive electrode conductive agent further includes carbon black particles; the mass percentage of the positive electrode conductive agent is 0.4% to 2.5% based on the mass of the positive electrode active material layer. After adsorbing the binder, the carbon black particles are easily distributed on the surface of the positive electrode active material layer, further enhancing the conductivity of the positive electrode conductive agent. Further introducing carbon black particles into the positive electrode conductive agent and controlling the content of the carbon black particles within the aforementioned range is beneficial for the carbon nanotubes and carbon black particles to work together to form a conductive network with good continuity and conductivity, further improving the conductivity of the positive electrode sheet.
[0015] In one embodiment of this application, the positive electrode active material layer further includes a binder, which includes at least one selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyamide, polyethylene ether, polymethyl methacrylate, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene rubber, polypropylene, polyethylene, polytetrafluoroethylene, polyetherimide, hydrogenated nitrile rubber, or carboxymethyl cellulose salt; based on the positive electrode active material layer, the mass percentage content of the binder is 0.8% to 3%. The above-mentioned binders have good adhesion. By selecting the above-mentioned types of binders and controlling the content of the binder in the positive electrode active material layer within the above-mentioned range, the positive electrode sheet has high cohesion and conductivity. The secondary battery using the positive electrode sheet has low internal resistance and thickness expansion rate.
[0016] In one embodiment of this application, the positive electrode active material layer further includes a positive electrode active material, which includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium-rich manganese-based materials, or lithium titanate; based on the mass of the positive electrode active material layer, the mass percentage content of the positive electrode active material is 96.1% to 98.8%. By selecting the above-mentioned types of positive electrode active materials and controlling the content of the positive electrode active material within the above-mentioned range, the secondary battery can have a high energy density while having a low internal resistance.
[0017] A second aspect of this application provides a secondary battery comprising the positive electrode sheet described in any of the foregoing embodiments. Therefore, the secondary battery has a low internal resistance.
[0018] A third aspect of this application provides an electronic device comprising the secondary battery described in any of the foregoing embodiments. Therefore, the electronic device exhibits good performance.
[0019] The beneficial effects of this application are:
[0020] This application provides a positive electrode, a secondary battery, and an electronic device. The positive electrode uses carbon nanotubes with a dendritic structure, and the diameter of the carbon nanotubes and the length of the longest branch are controlled within the range specified in this application. This ensures the continuity of the conductive network formed by the carbon nanotubes, improves electron transport efficiency, and enriches the transport paths of lithium ions along the surface of the carbon nanotubes. Furthermore, the carbon nanotubes in this application have a dendritic structure, resulting in more uniform dispersion than non-dendritic carbon nanotubes. This allows for better uniformity and thinness when coated on the surface of the positive electrode active material, making it easier to achieve good conductivity. Therefore, the positive electrode has excellent conductivity, and when used in a secondary battery, the battery exhibits lower internal resistance. Detailed Implementation
[0021] To make the objectives, technical solutions, and advantages of this application clearer, the following embodiments are provided to further illustrate this application in detail. Obviously, the described embodiments are merely some embodiments of this application, and not all embodiments. All other embodiments obtained by those skilled in the art based on this application are within the scope of protection of this application.
[0022] It should be noted that, in the specific embodiments of this application, lithium-ion batteries are used as an example of secondary batteries to explain this application, but the secondary batteries in this application are not limited to lithium-ion batteries.
[0023] The first aspect of this application provides a positive electrode sheet, which includes a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector. The phrase "positive active material layer disposed on at least one surface of the positive current collector" means that the positive active material layer can be disposed on one or both surfaces of the positive current collector along its thickness direction. The "surface" can be a portion of the surface of the positive current collector or the entire surface of the positive current collector. The positive active material layer includes a positive conductive agent, which includes carbon nanotubes with a dendritic structure. The diameter of the carbon nanotubes is 3 nm to 15 nm; the length of the longest branch in the carbon nanotube is 5 μm to 30 μm.
[0024] For example, the diameter of carbon nanotubes is 3nm, 4nm, 5nm, 6nm, 7nm, 8nm, 9nm, 10nm, 12nm, 13nm, 15nm, or any value between any two of the above ranges. When the diameter of carbon nanotubes is less than 3 nm, the nanotubes are too small and too thin, resulting in uneven dispersion in the positive electrode slurry. After the positive electrode slurry is coated onto the surface of the positive electrode current collector to form the positive electrode active material layer, the uneven distribution of carbon nanotubes within this layer reduces the probability of forming a well-connected conductive network, thus affecting the conductivity of the positive electrode conductive agent and leading to poor conductivity of the positive electrode sheet. When the diameter of carbon nanotubes is greater than 15 nm, the nanotubes are too large and too thick, resulting in excessive thickness on the surface of the positive electrode active material. This excessive thickness reduces the specific surface area, leading to a decrease in the effective conductive area. Furthermore, at the same content, excessively thick carbon nanotubes result in too few nanotubes distributed in the positive electrode active material layer, affecting the continuity of the conductive network and consequently impacting the conductivity of the positive electrode sheet.
[0025] For example, the longest branch length in a carbon nanotube can be 5 μm, 7 μm, 10 μm, 12 μm, 15 μm, 18 μm, 20 μm, 22 μm, 25 μm, 27 μm, 30 μm, or any value within any two of these ranges. If the longest branch length is less than 5 μm, the branch length is too short, which is not conducive to the formation of a coherent conductive network and reduces the probability of improving the conductivity of the positive electrode. If the longest branch length is greater than 30 μm, the branch length is too long, and the carbon nanotubes will be unevenly dispersed in the positive electrode slurry during preparation. This is not conducive to the uniform distribution of carbon nanotubes in the positive electrode active material layer, and thus the probability of forming a good coherent conductive network is too low, which will affect the conductivity of the positive electrode conductive agent and result in poor conductivity of the positive electrode.
[0026] The positive electrode of this application uses the aforementioned carbon nanotubes as the positive electrode conductive agent and controls the diameter of the carbon nanotubes and the length of the longest branch within the carbon nanotubes within the range of this application. This makes the conductive network formed by the carbon nanotubes coherent, improves the electron transport efficiency, and enhances the conductivity of lithium ions (Li). + The transport paths along the surface of carbon nanotubes are more abundant. Furthermore, the carbon nanotubes of this application have a dendritic structure, resulting in more uniform dispersion than non-dendritic carbon nanotubes. This allows for better uniformity and thinness when coated on the surface of the positive electrode active material, making it easier to achieve good conductivity. Therefore, through the above configuration, the positive electrode sheet exhibits good conductivity, and when used in a secondary battery, the secondary battery has lower internal resistance.
[0027] In one embodiment of this application, the different branches of carbon nanotubes are connected by molecular covalent bonds. The carbon nanotubes with a dendritic structure formed by the molecular covalent bonds connecting the different branches can exist as a whole, exhibiting good stability. When used as a positive electrode conductive agent, they have low impedance and provide good conductivity.
[0028] In one embodiment of this application, the diameter of the carbon nanotubes is between 5 nm and 10 nm. For example, the diameter of the carbon nanotubes is 5 nm, 6 nm, 7 nm, 8 nm, 9 nm, 10 nm, or any value between any two of the above ranges. Controlling the diameter of the carbon nanotubes within this range facilitates their uniform distribution in the positive electrode slurry. After the positive electrode slurry is coated onto the surface of the positive electrode current collector to form a positive electrode active material layer, the carbon nanotubes are uniformly distributed within the positive electrode active material layer, which is beneficial for the conductivity of the carbon nanotubes, resulting in good conductivity of the positive electrode and good electron and lithium ion transport efficiency. When the positive electrode is applied to a secondary battery, the secondary battery exhibits lower internal resistance.
[0029] In one embodiment of this application, the length of the longest branch in the carbon nanotube is between 8 μm and 20 μm. For example, the length of the longest branch in the carbon nanotube is 8 μm, 10 μm, 11 μm, 12 μm, 15 μm, 17 μm, 18 μm, 20 μm, or any value between any two of the above ranges. Controlling the length of the longest branch in the carbon nanotube within the above range is beneficial for the uniform distribution of carbon nanotubes in the positive electrode slurry. After the positive electrode slurry is coated onto the surface of the positive electrode current collector to form a positive electrode active material layer, the carbon nanotubes are uniformly distributed within the positive electrode active material layer. This also facilitates the uniform and thin distribution of carbon nanotubes on the surface of the positive electrode active material, forming a conductive network with good continuity and improving the conductivity of the positive electrode sheet. When the positive electrode sheet is applied to a secondary battery, the secondary battery has a lower internal resistance.
[0030] In one embodiment of this application, the mass percentage of carbon nanotubes is 0.05% to 2% based on the mass of the positive electrode active material layer. For example, the mass percentage of carbon nanotubes is 0.05%, 0.1%, 0.3%, 0.7%, 0.8%, 1%, 1.2%, 1.4%, 1.5%, 1.7%, 1.9%, 2%, or any value between any two of the above ranges. The carbon nanotubes of this application have a fine diameter and are easy to form a coherent conductive network; a small amount added can achieve good conductivity. Controlling the mass percentage of carbon nanotubes within the above range is beneficial for forming a good coherent conductive network of carbon nanotubes without affecting the content of other components in the positive electrode active material layer, resulting in good conductivity of the positive electrode and good electron and lithium-ion transport efficiency. When the positive electrode is applied to a secondary battery, the secondary battery has a low internal resistance.
[0031] In one embodiment of this application, the mass percentage of carbon nanotubes is 0.1% to 0.5%. For example, the mass percentage of carbon nanotubes is 0.1%, 0.2%, 0.3%, 0.4%, 0.5%, or any value between any two of the above ranges. Controlling the mass percentage of carbon nanotubes within the above range is beneficial for increasing the content of the positive electrode active material while providing good conductivity, thereby increasing the energy density of the secondary battery using the positive electrode sheet while maintaining low internal resistance.
[0032] In one embodiment of this application, the carbon nanotubes have 3 to 10 branches. For example, the carbon nanotubes may have 3, 4, 5, 6, 7, 8, 9, or 10 branches, or any value between any two of the above ranges. Controlling the branching of the carbon nanotubes within these ranges results in good dispersion uniformity, which is beneficial for the uniform distribution of carbon nanotubes in the positive electrode slurry and the positive electrode active material layer. It also facilitates a more uniform and thinner coating of carbon nanotubes on the surface of the positive electrode active material. The carbon nanotubes form a well-connected conductive network, providing abundant transport paths for lithium ions along the surface of the carbon nanotubes, resulting in faster lithium ion transport efficiency and good conductivity of the positive electrode. The secondary battery using the positive electrode exhibits lower internal resistance.
[0033] In one embodiment of this application, the carbon nanotubes have 4 to 10 carbon layers. For example, the number of carbon layers in the carbon nanotubes can be 4, 5, 6, 7, 8, 9, or 10 layers, or any value between any two of the above ranges. Controlling the number of carbon layers within this range facilitates a more uniform and thinner coating of carbon nanotubes on the surface of the positive electrode active material, allowing the carbon nanotubes to form a well-connected conductive network, resulting in faster lithium-ion transport efficiency and better conductivity of the positive electrode. The secondary battery using this positive electrode exhibits lower internal resistance.
[0034] In one embodiment of this application, the positive electrode active material layer further includes a positive electrode active material, and carbon nanotubes are disposed on the surface of the positive electrode active material particles. The thickness of the carbon nanotubes disposed on the surface of the positive electrode active material is 5 nm to 20 nm. For example, the thickness of the carbon nanotubes disposed on the surface of the positive electrode active material is 5 nm, 7 nm, 8 nm, 9 nm, 10 nm, 12 nm, 15 nm, 17 nm, 18 nm, 19 nm, 20 nm, or any value between any two of the above ranges. Controlling the thickness of the carbon nanotubes disposed on the surface of the positive electrode active material within the above range is beneficial for the rapid migration of electrons and ions to the surface of the positive electrode active material, thereby helping the secondary battery using the positive electrode sheet to have a lower internal resistance.
[0035] This application does not impose any particular restrictions on the method for controlling the thickness of carbon nanotubes on the surface of the positive electrode active material, as long as the purpose of this application can be achieved. For example, it can be achieved by controlling at least one of the diameter or content of carbon nanotubes. Generally speaking, when the content of carbon nanotubes is constant, the larger the diameter of the carbon nanotubes, the thicker the carbon nanotubes are on the surface of the positive electrode active material; when the diameter of the carbon nanotubes is constant, the higher the content of carbon nanotubes, the thicker the carbon nanotubes are on the surface of the positive electrode active material.
[0036] In one embodiment of this application, the distance between two adjacent carbon nanotubes disposed on the surface of the positive electrode active material is d, and the coefficient of variation of d is 0.5% to 5%. For example, the coefficient of variation of d is 0.5%, 0.7%, 1.0%, 1.1%, 1.7%, 2.0%, 2.1%, 2.4%, 3.0%, 3.7%, 4.0%, 4.3%, 4.7%, 5%, or any value between any two of the above ranges. Controlling the coefficient of variation of d within the above range indicates that the carbon nanotubes are uniformly distributed on the surface of the positive electrode active material, which is beneficial for forming a coherent and uniform conductive network, thereby contributing to good conductivity of the positive electrode and lower internal resistance in the secondary battery using the positive electrode. In this application, "the distance d between two adjacent carbon nanotubes" refers to the vertical distance between the centers of two adjacent carbon nanotubes.
[0037] This application does not impose any particular restrictions on the method of controlling the coefficient of variation of d, as long as it achieves the purpose of this application. For example, it can be achieved by controlling at least one of the following: the diameter of the carbon nanotube, the length of the longest branch, the number of branches, the number of carbon layers, or the amount added. Generally speaking, if either the diameter of the carbon nanotube or the number of carbon layers is constant, the larger the other, the smaller the coefficient of variation of d; the longer the length of the longest branch, the larger the coefficient of variation of d; the more branches, the larger the coefficient of variation of d; and the greater the amount of carbon nanotubes added, the smaller the coefficient of variation of d.
[0038] In one embodiment of this application, the positive electrode conductive agent further includes carbon black particles; the mass percentage of the positive electrode conductive agent is 0.4% to 2.5% based on the mass of the positive electrode active material layer. For example, the mass percentage of the positive electrode conductive agent is 0.4%, 0.6%, 0.8%, 1.0%, 1.1%, 1.4%, 1.5%, 1.7%, 1.8%, 1.9%, 2.1%, 2.2%, 2.3%, 2.5%, or any value between any two of the above ranges. After adsorbing the binder, the carbon black particles are easily distributed on the surface of the positive electrode active material layer, further improving the conductivity of the positive electrode conductive agent. Further introducing carbon black particles into the positive electrode conductive agent and controlling the content of the carbon black particles within the above range is beneficial for the carbon nanotubes and carbon black particles to cooperate and form a conductive network with good continuity and conductivity, further improving the conductivity of the positive electrode sheet. This further reduces the internal resistance of the secondary battery using the positive electrode sheet.
[0039] This application does not impose any particular limitation on the content of carbon black particles, as long as the purpose of this application can be achieved. For example, based on the mass of the positive electrode active material layer, the mass percentage of carbon black particles can be 0.01% to 2%.
[0040] In one embodiment of this application, the positive electrode active material layer further includes a binder, which includes at least one selected from polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyamide, polyethylene ether, polymethyl methacrylate, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene rubber, polypropylene, polyethylene, polytetrafluoroethylene, polyetherimide, hydrogenated nitrile rubber, or carboxymethyl cellulose salt. Based on the positive electrode active material layer, the mass percentage content of the binder is from 0.8% to 3%. For example, the mass percentage content of the binder is 0.8%, 1.0%, 1.2%, 1.4%, 1.5%, 1.7%, 1.8%, 2.0%, 2.2%, 2.5%, 2.8%, 3%, or any value between any two of the above ranges. The aforementioned binders possess excellent adhesion. Selecting these types of binders and controlling their content within the specified range in the positive electrode active material layer facilitates a match between the content of the positive electrode conductive agent and the binder. This allows for easy and uniform distribution of the positive electrode conductive agent, resulting in excellent conductivity of the positive electrode sheet. Furthermore, it ensures good adhesion between the particles of the positive electrode active material and between the positive electrode active material layer and the positive electrode current collector. This also allows for the inclusion of more positive electrode active material in the positive electrode active material layer, providing greater capacity for the positive electrode sheet. Consequently, the positive electrode sheet exhibits high cohesion and conductivity. Secondary batteries using this positive electrode sheet exhibit lower internal resistance and thickness expansion rate.
[0041] In one embodiment of this application, the positive electrode active material layer further includes a positive electrode active material, which includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium-rich manganese-based materials, or lithium titanate; based on the mass of the positive electrode active material layer, the mass percentage content of the positive electrode active material is 96.1% to 98.8%. For example, the mass percentage content of the positive electrode active material is 96.1%, 96.3%, 96.5%, 97.0%, 97.5%, 98.0%, 98.1%, 98.5%, 98.8%, or any value between any two of the above ranges. Selecting the above-mentioned types of positive electrode active materials and controlling the content of the positive electrode active material within the above range is beneficial to enabling the positive electrode active material layer to provide a larger capacity, and enabling the secondary battery to have a higher energy density while having a lower internal resistance.
[0042] This application does not impose any particular restrictions on the positive electrode current collector, as long as it achieves the purpose of this application. For example, the positive electrode current collector may comprise aluminum foil or aluminum alloy foil. In this application, there are no particular restrictions on the thickness of the positive electrode current collector and the positive electrode active material layer, as long as they achieve the purpose of this application. For example, the thickness of the positive electrode current collector is 5 μm to 20 μm. The thickness of the single-layer positive electrode active material layer is 30 μm to 120 μm.
[0043] This application does not impose any particular limitation on the preparation method of carbon black particles, as long as it achieves the purpose of this application. For example, the preparation method of carbon black particles includes, but is not limited to, the following steps: placing the raw material in a reactor and subjecting it to a pyrolysis reaction at a high temperature of 1000°C to 1500°C to generate carbon black particles; blowing the carbon black particles out of the furnace tube, cooling, and collecting them. This application does not impose any particular limitation on the type of raw material mentioned above, as long as it achieves the purpose of this application. For example, the raw material may include, but is not limited to, acetylene or tar.
[0044] This application does not impose any particular limitation on the preparation method of carbon nanotubes, as long as it achieves the purpose of this application. For example, the preparation method of carbon nanotubes includes, but is not limited to, the following steps: selecting a cobalt-based or iron-based catalyst, depositing the catalyst on a silicon substrate, and placing it in a reactor; introducing an inert protective gas into the reactor, and heating the reactor to 800°C to 1100°C; introducing a reactive gas into the reactor, and depositing the carbon formed by the cracking of the reactive gas in the reactor onto the catalyst to form carbon nanotubes with a dendritic structure; and dispersing the carbon nanotubes by sand milling to obtain the carbon nanotubes of this application. This application does not impose any particular limitation on the rotation speed of the above sand milling dispersion, as long as it achieves the purpose of this application. For example, the rotation speed is 900 r / min to 1300 r / min. This application does not impose any particular limitation on the type of inert gas mentioned above, as long as it achieves the purpose of this application. For example, inert gases include, but are not limited to, any of argon or nitrogen. This application does not impose any particular limitation on the type of reactive gas mentioned above, as long as it achieves the purpose of this application. For example, reactive gases include, but are not limited to, acetylene. This application does not impose any particular limitation on the type of cobalt-based catalyst mentioned above. Those skilled in the art can select one as needed, as long as the purpose of this application is achieved. For example, cobalt-based catalysts include, but are not limited to, cobalt-nickel alloys. This application also does not impose any particular limitation on the type of iron-based catalyst mentioned above. Those skilled in the art can select one as needed, as long as the purpose of this application is achieved. For example, iron-based catalysts include, but are not limited to, iron-magnesium alloys. This application does not impose any particular limitation on the mass ratio of catalyst to reactant gas, as long as the purpose of this application is achieved. For example, the mass ratio of catalyst to reactant gas is (0.5 to 2.0):100.
[0045] In this application, when different branches of carbon nanotubes are connected by molecular covalent bonds, the diameter and number of carbon layers of the carbon nanotubes can be controlled by changing the size of the catalyst particles during the preparation process. Generally, larger catalyst particles result in a larger carbon nanotube diameter and more carbon layers; smaller catalyst particles result in a smaller carbon nanotube diameter and fewer carbon layers. The length of the longest branch in the carbon nanotube can be controlled by changing the catalyst activity and synthesis temperature during the preparation process. Generally, higher activity and higher synthesis temperature result in a longer longest branch. The number of branches in the carbon nanotube can be controlled by changing the catalyst morphology and anisotropic activity during the preparation process. Generally, smaller anisotropic differences in the catalyst result in more branches.
[0046] The present application does not particularly limit the preparation method of the positive electrode sheet, and any preparation method well-known in the art can be adopted as long as the purpose of the present application can be achieved. For example, the preparation method of the positive electrode sheet includes but is not limited to the following steps: (2) Mix the positive electrode conductive agent, binder, and positive electrode active material evenly, add a solvent, and stir evenly to obtain a positive electrode slurry; (2) Coating the positive electrode slurry on one surface of the positive electrode current collector, drying and cold pressing to form a positive electrode sheet with a positive electrode active material layer provided on one side. In another embodiment, the preparation method of the positive electrode sheet includes the following steps: (1) Mix the positive electrode conductive agent, binder, and positive electrode active material evenly, add a solvent, and stir evenly to obtain a positive electrode slurry; (2) Coating the positive electrode slurry on one surface of the positive electrode current collector, drying to form a positive electrode active material layer; (3) Repeating step (2) on the other surface of the positive electrode current collector, and cold pressing and slitting to obtain a positive electrode sheet with positive electrode active material layers provided on both sides. The present application does not particularly limit the solid content of the positive electrode slurry as long as the purpose of the present application can be achieved. For example, the solid content of the positive electrode slurry is 50 wt% to 80 wt%. The present application does not particularly limit the type of the above solvent as long as the purpose of the present application can be achieved. For example, the solvent may include but is not limited to N-methylpyrrolidone (NMP) or deionized water.
[0047] The second aspect of the present application provides a secondary battery, which includes the positive electrode sheet described in any of the foregoing embodiments. The positive electrode sheet has good conductivity, so the secondary battery has a lower internal resistance.
[0048] In an embodiment of the present application, the secondary battery includes a negative electrode sheet. The present application does not particularly limit the negative electrode sheet as long as the purpose of the present application can be achieved. In one embodiment, the negative electrode sheet includes a negative electrode current collector and a negative electrode active material layer, and the negative electrode active material layer is provided on one surface or both surfaces of the negative electrode current collector. The above "surface" may be a partial surface of the negative electrode current collector or the entire surface of the negative electrode current collector. The present application does not particularly limit the negative electrode current collector as long as the purpose of the present application can be achieved. For example, the negative electrode current collector may include copper foil, copper alloy foil, nickel foil, stainless steel foil, titanium foil, nickel foam or copper foam, etc. The negative electrode active material layer of the present application contains a negative electrode active material. The present application does not particularly limit the type of the negative electrode active material as long as the purpose of the present application can be achieved. For example, the negative electrode active material may include natural graphite, artificial graphite, mesocarbon microbeads (MCMB), hard carbon, soft carbon, silicon, silicon-carbon composite, SiO x (0 < x < 2), Li-Sn alloy, Li-Sn-O alloy, Sn, SnO, SnO2, spinel-structured lithium titanate Li4Ti5O 12The negative electrode active material layer contains at least one of the following: Li-Al alloy or metallic lithium. In this application, there are no particular limitations on the thickness of the negative electrode current collector or the negative electrode active material layer, as long as the purpose of this application is achieved. For example, the thickness of the negative electrode current collector is 6 μm to 10 μm, and the thickness of the negative electrode active material layer is 30 μm to 130 μm. Optionally, the negative electrode active material layer may further include at least one of the following: a negative electrode conductive agent, a dispersant, or a negative electrode binder. This application does not particularly limit the types of negative electrode conductive agents, dispersants, and negative electrode binders in the negative electrode active material layer, as long as the purpose of this application is achieved. This application does not particularly limit the mass ratio of the negative electrode active material, negative electrode conductive agent, dispersant, and negative electrode binder in the negative electrode active material layer, as long as the purpose of this application is achieved. For example, the mass ratio of the negative electrode active material, negative electrode conductive agent, dispersant, and negative electrode binder in the negative electrode active material layer is (96–98):(0.5–2):(0–1.5):(1.0–1.9).
[0049] In one embodiment of this application, the secondary battery includes a separator disposed between the positive electrode and the negative electrode to separate the positive and negative electrodes, prevent internal short circuits in the secondary battery, allow electrolyte ions to pass freely, and not affect the electrochemical charging and discharging process. This application does not impose any particular limitation on the separator, as long as it achieves the purpose of this application. For example, the separator material may include, but is not limited to, at least one of polyethylene (PE), polyolefins (PO) primarily composed of polypropylene (PP), polyester (e.g., polyethylene terephthalate (PET) film), cellulose, polyimide (PI), polyamide (PA), spandex, or aramid. The separator type may include at least one of woven membrane, nonwoven membrane, microporous membrane, composite membrane, rolled membrane, or spun membrane. This application does not impose any particular limitation on the separator thickness, as long as it achieves the purpose of this application.
[0050] In one embodiment of this application, the secondary battery includes an electrolyte. This application does not impose any particular limitation on the type of electrolyte; those skilled in the art can select any electrolyte known in the art according to actual needs, as long as it achieves the purpose of this application.
[0051] In one embodiment of this application, the secondary battery includes a packaging bag for containing the positive electrode, negative electrode, separator, and electrolyte. This application does not impose any particular limitation on the type of packaging bag; those skilled in the art can select any packaging bag known in the art according to actual needs, as long as it achieves the purpose of this application.
[0052] The secondary battery described in this application is not particularly limited and may include any device in which an electrochemical reaction occurs. For example, a secondary battery may include, but is not limited to, a lithium metal secondary battery, a lithium-ion secondary battery (lithium-ion battery), a lithium polymer secondary battery, or a lithium-ion polymer secondary battery.
[0053] This application does not impose any particular limitation on the preparation method of the secondary battery. Any preparation method known in the art can be used, as long as it can achieve the purpose of this application. For example, the preparation method of the secondary battery includes, but is not limited to, the following steps: stacking the separator, positive electrode, separator and negative electrode in sequence, and winding, folding or other operations as needed to obtain a wound electrode assembly; placing the electrode assembly in a packaging bag; injecting electrolyte into the packaging bag and sealing it to obtain a secondary battery; or stacking the separator, positive electrode, separator and negative electrode in sequence, and then fixing the four corners of the entire stacked structure to obtain a stacked electrode assembly; placing the electrode assembly in a packaging bag; injecting electrolyte into the packaging bag and sealing it to obtain a secondary battery.
[0054] A third aspect of this application provides an electronic device comprising the secondary battery described in any of the foregoing embodiments. Therefore, the electronic device exhibits good performance.
[0055] The electronic device described in this application is not particularly limited and can be any electronic device known in the prior art. For example, the electronic device may include, but is not limited to: laptop computers, pen input computers, mobile computers, e-book players, portable telephones, portable fax machines, portable copiers, portable printers, stereo headphones, video recorders, LCD TVs, portable cleaners, portable CD players, mini CDs, transceivers, electronic notebooks, calculators, memory cards, portable recorders, radios, backup power supplies, motors, automobiles, motorcycles, electric bicycles, bicycles, lighting fixtures, toys, game consoles, clocks, power tools, flashlights, cameras, household large-capacity batteries, and lithium-ion capacitors.
[0056] Example
[0057] The embodiments and comparative examples provided below illustrate the implementation of this application in more detail. Various tests and evaluations were conducted according to the methods described below.
[0058] Test methods and equipment:
[0059] Testing of carbon nanotube diameter, longest branch length, number of branches, and thickness:
[0060] a) Discharge the lithium-ion battery at a constant current of 0.2C to 3.0V until it reaches full discharge. Then disassemble the lithium-ion battery to obtain the positive electrode.
[0061] b) Soak the positive electrode in DMC at room temperature for 60 minutes, remove it, and air dry at room temperature;
[0062] c) Take the positive electrode sheet and immerse it in the solvent N-methylpyrrolidone (NMP) until the positive electrode sheet is delaminated. Then, take out the positive current collector at room temperature, filter the positive active material layer out of the solvent and dry it.
[0063] d) Take the dried material from c) and use concentrated sulfuric acid to corrode the positive electrode active material and binder, then filter and dry to obtain the positive electrode conductive agent;
[0064] e) After fully diluting the positive electrode conductive agent, coat it on aluminum foil and dry it. Observe the carbon nanotubes under SEM and test the longest branch length, number of branches, and branch diameter of 30 carbon nanotubes with dendritic structures. Then, the average value of each parameter is the mean value.
[0065] f) Take the positive electrode conductive agent from d) and observe the number and thickness of the branched carbon nanotube wall layers under SEM. Test 10 samples and take the average value as the final value.
[0066] Test of the coefficient of variation of d:
[0067] 1) Discharge the lithium-ion battery at a constant current of 0.2C to 3.0V until it reaches full discharge. Then disassemble the lithium-ion battery to obtain the positive electrode.
[0068] 2) Soak the positive electrode in DMC at room temperature for 60 minutes, then remove and air dry at room temperature;
[0069] 3) Obtain the cross-section of the positive electrode sheet by liquid nitrogen brittle fracture. Observe and test the distance d between adjacent carbon nanotubes on the surface of the positive electrode active material particles in the cross-section using SEM. Test 50 data points, and then calculate the standard deviation σ and mean R of these data points. Then the coefficient of variation of d = 3σ / R.
[0070] Testing the internal resistance of lithium-ion batteries:
[0071] The lithium-ion battery was placed in a constant temperature chamber at 25°C for 120 minutes, charged at a constant current rate of 1C to 4.5V, then charged at a constant voltage rate until the current was less than or equal to 0.02C. It was then left to stand for 30 minutes, discharged at a current of 0.1C for 10 seconds (taking a sample every 0.1 seconds and recording the corresponding voltage value U11), and discharged at a current of 1C for 360 seconds (taking a sample every 0.1 seconds and recording the corresponding voltage value U12). This charge-discharge cycle was repeated 8 times. In the 8th cycle, the battery was discharged at a current of 0.1C for 10 seconds (taking a sample every 0.1 seconds and recording the corresponding voltage value U81), and discharged at a current of 1C for 360 seconds (taking a sample every 0.1 seconds and recording the corresponding voltage value U82).
[0072] The 360s DCR at 20% SOC (State of Charge) is calculated using the following formula: R = (U81 - U82) / (1C - 0.1C).
[0073] Test method for lithium-ion batteries to experience 80% capacity decay during 45℃ cycling:
[0074] Take the finished lithium-ion batteries and perform the following tests at (45±2)℃:
[0075] Let it stand for 2 hours, then discharge it at 0.7C to 3.0V, and let it stand for 5 minutes.
[0076] [Charge at 1.0C to 4.5V, then charge at 4.5V to 0.05C; let stand for 5 minutes; discharge at 0.5C to 3.0V, record the discharge capacity of this step as C1; let stand for 5 minutes;]
[0077] The process in brackets [ ] is repeated 49 times, with the lithium-ion battery discharge capacities recorded sequentially as C1, C2, C3...C49; in cycle 50, the battery is charged at 1.0C to 4.5V, then charged at 4.5V to 0.05C; left to stand for 5 minutes; then discharged at 0.2C to 3.0V, with the discharge capacity recorded as C50. This process is repeated sequentially, with cycle numbers C51, C51...C1000. The cycle number where the ratio of capacity to C3 is (80% ± 0.2%) is found. If multiple cycle numbers meet the requirement, the average of these is taken as the final result. A higher cycle number indicates better cycle performance of the lithium-ion battery.
[0078] Example 1-1
[0079] <Preparation of the positive electrode>
[0080] Preparation of carbon nanotubes: A cobalt-nickel alloy was selected as the catalyst and deposited on a silicon substrate in a reactor. Argon gas was introduced into the reactor, and the reactor temperature was adjusted to 900℃. Acetylene was introduced into the reactor, and the carbon formed by the cracking of acetylene in the reactor was deposited and grown on the catalyst to form carbon nanotubes with a dendritic structure. The nanotubes were dispersed by sand milling to obtain carbon nanotubes of suitable specifications for later use. The milling speed was 1300 r / min. The mass ratio of catalyst to acetylene was 1:100.
[0081] Lithium cobalt oxide (CCO), a positive electrode active material, a positive electrode conductive agent, and polyvinylidene fluoride (PVDF, weight-average molecular weight 85W) binder were mixed, and N-methylpyrrolidone (NMP) was added as a solvent. The mixture was stirred under vacuum until a homogeneous positive electrode slurry with a solid content of 75 wt% was obtained. The positive electrode slurry was uniformly coated onto one surface of a 6 μm thick aluminum foil for the positive electrode current collector and dried at 90°C to obtain a positive electrode sheet with a single-sided coating of positive electrode active material. The above steps were then repeated on the other surface of the aluminum foil to obtain a positive electrode sheet with a double-sided coating of positive electrode active material. After cold pressing and slitting, positive electrode sheets with a size of 74 mm × 851 mm were obtained for later use.
[0082] The positive electrode conductive agent includes the carbon nanotubes prepared above. Based on the mass of the positive electrode active material layer, the mass percentage of the positive electrode active material is 98.3%, the mass percentage of the carbon nanotubes is 0.4%, and the mass percentage of the binder is 1.3%.
[0083] <Preparation of Negative Electrode Sheets>
[0084] The negative electrode active material is artificial graphite, the negative electrode conductive agent is acetylene black, and the negative electrode binder is styrene-butadiene rubber (SBR, with a weight average molecular weight of 5×10⁻⁶). 6 Carboxymethyl cellulose (CMC) and dispersant were mixed at a mass ratio of 96:2:1:1, and then deionized water was added as a solvent. The mixture was stirred under vacuum until a homogeneous negative electrode slurry with a solid content of 50 wt% was obtained. The negative electrode slurry was uniformly coated onto one surface of an 8 μm thick copper foil current collector and dried at 90°C to obtain a negative electrode sheet with a single-sided coating of negative electrode active material layer (130 μm thick). The above steps were then repeated on the other surface of the copper foil to obtain a negative electrode sheet with a double-sided coating of negative electrode active material layer. After cold pressing and slitting, negative electrode sheets with a size of 76 mm × 856 mm were obtained for later use.
[0085] <Preparation of the diaphragm>
[0086] A porous polyethylene (PE) membrane with a thickness of 8 μm was used as the diaphragm.
[0087] <Preparation of Electrolyte>
[0088] In a dry argon atmosphere, ethylene carbonate, methyl ethyl carbonate and diethyl carbonate were mixed in a mass ratio of 30:50:20 to obtain a basic electrolyte. Then, lithium hexafluorophosphate was added to the basic electrolyte, dissolved and mixed evenly to obtain an electrolyte with a lithium salt concentration of 1.15 mol / L.
[0089] <Preparation of Lithium-ion Batteries>
[0090] The separator, positive electrode, separator, and negative electrode are stacked in sequence and wound to obtain the electrode assembly. The electrode assembly is placed in an aluminum-plastic film packaging bag, dried, and then injected with electrolyte. After vacuum sealing, settling, formation, degassing, and edge trimming, a lithium-ion battery is obtained.
[0091] Examples 1-2 to Examples 1-9
[0092] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as in Examples 1-1.
[0093] Examples 1-10
[0094] Except for the addition of carbon black particles in the <Preparation of Positive Electrode Sheet> and the adjustment of the relevant preparation parameters according to Table 1, the rest is the same as in Example 1-1.
[0095] In the positive electrode active material layer, when the mass percentage of carbon black particles and carbon nanotubes changes, the mass percentage of positive electrode active material changes accordingly, while the mass percentage of binder remains unchanged. The sum of the mass percentages of carbon black particles, carbon nanotubes, positive electrode active material, and binder is 100%.
[0096] Examples 1-11 to Examples 1-29
[0097] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as in Examples 1-10.
[0098] In the positive electrode active material layers of Examples 1-11 to Examples 1-23 and Examples 1-25, when the mass percentage of carbon black particles and / or carbon nanotubes changes, the mass percentage of positive electrode active material changes accordingly, while the mass percentage of binder remains unchanged, and the sum of the mass percentages of carbon black particles, carbon nanotubes, positive electrode active material and binder is 100%.
[0099] In the positive electrode active material layers of Examples 1-24, when the mass percentage of carbon black particles and / or carbon nanotubes changes, the mass percentage of binder is adjusted to 0.8%, and the mass percentage of positive electrode active material is adjusted to 98.45%.
[0100] Examples 1-30
[0101] Except for replacing the carbon nanotubes in <Preparation of Positive Electrode Sheet> with carbon nanotubes with a dendritic structure formed by mutual attraction of van der Waals forces, the rest is the same as in Example 1-1.
[0102] The specific preparation method of carbon nanotubes with dendritic structures formed by mutual attraction of van der Waals forces is as follows:
[0103] Cobalt nanoparticles were selected as the catalyst and supported on a silica (SiO2) support, which was then placed in a reactor. An inert protective gas, nitrogen, was introduced into the reactor, and the temperature was raised to 800°C. Methane was then introduced into the reactor, causing an array of carbon nanotube bundles to form on the substrate. PVDF was used as a dispersant, and NMP was used as a solvent to mix the carbon nanotube bundles uniformly. The mixture was then milled in a sand mill at a flow rate of 12 kg / min for 90 min to form carbon nanotubes with the main trunks bound together by van der Waals forces and the ends individually dispersed into branched structures. The mass ratio of catalyst to methane was 0.8:100.
[0104] Examples 2-1 to 2-9
[0105] Except for adjusting the relevant preparation parameters according to Table 2, the rest is the same as in Examples 1-1.
[0106] Comparative Examples 1 to 6
[0107] Except for adjusting the relevant preparation parameters according to Table 1, the rest is the same as in Examples 1-1.
[0108] Comparative Example 7
[0109] Except for replacing the dendritic carbon nanotubes in <Preparation of Positive Electrode Sheet> with non-dendritic carbon nanotubes, everything else is the same as in Example 1-1.
[0110] Preparation of non-dendritic carbon nanotubes: Cobalt-based catalyst nanoparticles were supported on a silica (SiO2) carrier and placed in a reactor. An inert protective gas, nitrogen, was introduced into the reactor, and the reactor temperature was raised to 700°C. Ethylene, a reactive gas, was introduced into the reactor. The carbon formed by the cracking of the reactive gas in the reactor was deposited on the catalyst to form clustered carbon nanotube bundles. The bundles were then dispersed by high-speed sand milling to obtain single, dispersed non-dendritic carbon nanotubes. The mass ratio of catalyst to reactive gas was 0.8:100.
[0111] The preparation parameters and performance data of each embodiment and comparative example are shown in Table 1 and Table 2.
[0112] Table 1
[0113] Note: The “\” in Table 1 indicates that the carbon nanotubes in Comparative Example 7 are non-dendritic carbon nanotubes, and therefore have no interbranch connection.
[0114] As can be seen from Examples 1-1 to 1-30 and Comparative Examples 1 to 7, the secondary batteries of this application, by selecting carbon nanotubes with a dendritic structure and controlling the diameter of the carbon nanotubes and the length of the longest branch within the carbon nanotubes within the range of this application, achieve lower internal resistance and higher cycle performance. In contrast, the secondary batteries of the comparative examples, by selecting at least one of the diameter of the carbon nanotubes or the length of the longest branch within the carbon nanotubes outside the range of this application, achieve higher internal resistance and poorer cycle performance.
[0115] As can be seen from Examples 1-1 to 1-6, the number of carbon layers in the carbon nanotubes and the thickness of the carbon nanotubes on the surface of the positive electrode active material increase with the increase of the carbon nanotube diameter, while the coefficient of variation of d decreases with the increase of the carbon nanotube diameter. The carbon nanotube diameter typically affects the internal resistance and cycle performance of the secondary battery. As can be seen from Examples 1-1 to 1-6, when a secondary battery with a carbon nanotube diameter within the range of this application is selected, the number of carbon layers and the thickness of the carbon nanotubes on the surface of the positive electrode active material are also within the range of this application, resulting in a secondary battery with lower internal resistance and better cycle performance.
[0116] The length of the longest branch in carbon nanotubes usually affects the internal resistance and cycle performance of secondary batteries. As can be seen from Examples 1-1, 1-7 to 1-12, secondary batteries with the longest branch in carbon nanotubes within the range of this application have lower internal resistance and better cycle performance.
[0117] The mass percentage of carbon nanotubes in the positive electrode active material layer typically affects the internal resistance and cycle performance of a secondary battery. As can be seen from Examples 1-1, 1-13 to 1-20, secondary batteries with a carbon nanotube mass percentage in the positive electrode active material layer within the scope of this application exhibit lower internal resistance and better cycle performance. While Examples 1-17 have lower internal resistance compared to Examples 1-1, 1-13 to 1-20, the carbon nanotube content in Examples 1-17 increases the viscosity of the positive electrode slurry during preparation, making it difficult to coat the slurry onto the surface of the positive electrode current collector. This further complicates the processing of the positive electrode sheet and increases the production cost of the secondary battery.
[0118] The number of branches in carbon nanotubes typically affects the internal resistance and cycle performance of secondary batteries. As seen in Examples 1-1, 1-21 to 1-24, secondary batteries with a branch number within the scope of this application exhibit lower internal resistance and better cycle performance. While Examples 1-22 have lower internal resistance compared to Examples 1-1, 1-21 to 1-24, the higher branch number of the carbon nanotubes in Examples 1-22 increases the viscosity of the positive electrode slurry during preparation, making it difficult to coat the slurry onto the surface of the positive electrode current collector. This further complicates the processing of the positive electrode sheet and increases the production cost of the secondary battery.
[0119] Further introducing carbon black particles into the positive electrode conductive agent, the mass percentage of the positive electrode conductive agent in the positive electrode active material layer usually affects the internal resistance and cycle performance of the secondary battery. As can be seen from Examples 1-1, 1-13 to 1-20, and 1-25 to 1-29, when carbon black particles are selected, the secondary battery with the mass percentage of the positive electrode conductive agent in the positive electrode active material layer within the scope of this application has lower internal resistance and better cycle performance. Among them, although Example 1-13 has a lower internal resistance than Examples 1-20 and 1-25 to 1-29, the carbon nanotubes in Example 1-17 will increase the viscosity of the positive electrode slurry during preparation, making it difficult to coat the positive electrode slurry on the surface of the positive electrode current collector, making the processing of the positive electrode sheet more difficult, and increasing the production cost of the secondary battery.
[0120] Table 2
[0121] The type of binder usually affects the internal resistance of a secondary battery. As can be seen from Examples 1-1, 2-1 to 2-3, secondary batteries using binders within the scope of this application have lower internal resistance.
[0122] The mass percentage of binder in the positive electrode active material layer usually affects the internal resistance of the secondary battery. As can be seen from Examples 1-1, 2-4 and 2-7, the secondary battery with the mass percentage of binder in the positive electrode active material layer within the scope of this application has a lower internal resistance.
[0123] The type of positive electrode active material and its mass percentage in the positive electrode active material layer usually affect the internal resistance of the secondary battery. As can be seen from Examples 1-1, 2-1 to 2-9, the secondary battery with the type of positive electrode active material and its mass percentage in the positive electrode active material layer within the scope of this application has a lower internal resistance.
[0124] It should be noted that, in this document, relational terms such as "first" and "second" are used only to distinguish one entity or operation from another, and do not necessarily require or imply any such actual relationship or order between these entities or operations. Furthermore, the terms "comprising," "including," or any other variations thereof are intended to cover non-exclusive inclusion, such that a process, method, article, or apparatus that comprises a list of elements includes not only those elements but also other elements not expressly listed, or elements inherent to such process, method, article, or apparatus.
[0125] The various embodiments in this specification are described in a related manner. The same or similar parts between the various embodiments can be referred to each other. Each embodiment focuses on describing the differences from other embodiments.
[0126] The above description is only a preferred embodiment of this application and is not intended to limit this application. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of this application should be included within the scope of protection of this application.
Claims
1. A positive electrode sheet, comprising a positive current collector and a positive active material layer disposed on at least one surface of the positive current collector, the positive active material layer comprising a positive conductive agent, the positive conductive agent comprising carbon nanotubes having a dendritic structure; The diameter of the carbon nanotubes is 3 nm to 15 nm; The longest branch in the carbon nanotube is between 5 μm and 30 μm.
2. The positive electrode sheet according to claim 1, wherein, Based on the mass of the positive electrode active material layer, the mass percentage of the carbon nanotubes is 0.05% to 2%.
3. The positive electrode sheet according to claim 2, wherein, The positive electrode sheet satisfies at least one of the following characteristics: (1) The diameter of the carbon nanotubes is 5 nm to 10 nm; (2) The longest branch in the carbon nanotube is 8 μm to 20 μm in length; (3) The carbon nanotubes have a mass percentage content of 0.1% to 0.5%.
4. The positive electrode sheet according to claim 1, wherein, The carbon nanotubes have 3 to 10 branches.
5. The positive electrode sheet according to claim 1, wherein, The carbon nanotubes have 4 to 10 carbon layers.
6. The positive electrode sheet according to claim 1, wherein, The different branches of the carbon nanotubes are connected by molecular covalent bonds.
7. The positive electrode sheet according to claim 1, wherein, The positive electrode active material layer further includes a positive electrode active material, and the carbon nanotubes are disposed on the surface of the positive electrode active material particles, with the thickness of the carbon nanotubes disposed on the surface of the positive electrode active material being 5 nm to 20 nm.
8. The positive electrode sheet according to claim 5, wherein, The spacing between two adjacent carbon nanotubes disposed on the surface of the positive electrode active material is d, and the coefficient of variation of d is 0.5% to 5%.
9. The positive electrode sheet according to claim 1, wherein, The positive electrode conductive agent also includes carbon black particles; Based on the mass of the positive electrode active material layer, the mass percentage of the positive electrode conductive agent is 0.4% to 2.5%.
10. The positive electrode sheet according to claim 1, wherein, The positive electrode active material layer further includes a binder, which includes at least one of polyvinylidene fluoride, polyvinylidene fluoride-hexafluoropropylene copolymer, polyacrylonitrile, polyacrylate, polyacrylic acid, polyacrylate, polyvinylpyrrolidone, polyamide, polyethylene ether, polymethyl methacrylate, polytetrafluoroethylene, polyhexafluoropropylene, styrene-butadiene rubber, polypropylene, polyethylene, polytetrafluoroethylene, polyetherimide, hydrogenated nitrile butadiene rubber, or carboxymethyl cellulose salt. Based on the positive electrode active material layer, the binder has a mass percentage content of 0.8% to 3%.
11. The positive electrode sheet according to claim 1, wherein, The positive electrode active material layer further includes a positive electrode active material, which includes at least one of lithium cobalt oxide, lithium manganese oxide, lithium nickel oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, lithium iron phosphate, lithium manganese iron phosphate, lithium vanadium phosphate, lithium-rich manganese-based materials, or lithium titanate. Based on the mass of the positive electrode active material layer, the mass percentage of the positive electrode active material is between 96.1% and 98.8%.
12. A secondary battery, wherein, The secondary battery includes the positive electrode sheet according to any one of claims 1 to 11.
13. An electronic device, wherein, The electronic device includes the secondary battery as described in claim 12.